2010
DOI: 10.1002/cbm.761
|View full text |Cite
|
Sign up to set email alerts
|

Personal aspirations and concerns inventory for offenders: Developments in the measurement of offenders' motivation

Abstract: Consistency with previous evidence, together with positive feedback, suggests that the PACI-O was acceptable with an offender population. Future research is required to assess the psychometric properties of the PACI-O, and to evaluate its potential as an assessment of offender motivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Analysis of the psychometric properties of the PACI‐O and its immediate precursor, the PCI‐OA, confirmed that a similar two factor structure existed in offender samples, but that indices from the original PCI (i.e. excluding the prison/offending specific indices) produced factors with more robust psychometric properties (Campbell et al, ; McMurran et al, ; Sellen et al, , ). The predictive validity of the PCI‐OA has also been established, whereby improvements in adaptive motivation over the course of a treatment programme have been observed (Sellen et al, ).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Analysis of the psychometric properties of the PACI‐O and its immediate precursor, the PCI‐OA, confirmed that a similar two factor structure existed in offender samples, but that indices from the original PCI (i.e. excluding the prison/offending specific indices) produced factors with more robust psychometric properties (Campbell et al, ; McMurran et al, ; Sellen et al, , ). The predictive validity of the PCI‐OA has also been established, whereby improvements in adaptive motivation over the course of a treatment programme have been observed (Sellen et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…One of the most theoretically rigorous instruments currently available to assess and enhance motivation in offenders is the Personal Aspirations and Concerns Inventory for Offenders (PACI‐O; Campbell et al, ). This is a relatively short, semi‐structured interview derived originally from the Personal Concerns Inventory (PCI; Cox and Klinger, ), and the Personal Concerns Inventory – Offender Adaptation (PCI‐OA; Sellen et al, ; Sellen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the PACIO has been developed as an assessment of motivation for engagement and behaviour change, Campbell et al (2010) have suggested it may have utility as a brief motivational intervention. Some of the reasons for this are that:…”
Section: Interventionmentioning
confidence: 99%